A modern approach to a unified field theory (Global Journal of Science Frontier Research, 2012)
This paper presents strictly the mathematical derivation of the Einstein field equations from a vanishing divergent field given Lie group SU(1) and satisfying cohomology, and a discussion of the implications of these results. Essentially, we obtain the expression from given postulates of a Quantum Yang-Mills theory- the gravitational terms reducing to when we have SU(1), satisfying ("good") cohomology (i.e. that of the standard formulation of Hodge's conjecture, [3] for a history), and we integrate with respect to the metric solution of the equations in a standard Lorentzian frame. We then discuss the implications of these results, and consider some misconceptions about past approaches to ubiquitous media.